Pupil-Generated Questions in a Collaborative Open Inquiry - Susanna Pöntinen; Sirpa Kärkkäinen; Kaisa Pihlainen; Sinikka Räty-Záborszky (MDPI AG, 2019)
Formulating questions is an integral part of pupils’ learning process and scientific inquiry. Investigating pupil-generated questions in a collaborative science learning setting, combining self-regulation theory and phases of inquiry, can extend the previous research into pupils’ questions. This study considered questions from pupils (n = 24, aged 11−12) as types of interaction to share and reflect on both their own and others’ ideas during a collaborative open inquiry. The study was qualitative in nature. The data was collected by making video recordings of pupils’ team discussions during the study process in 12 science lessons. A content analysis demonstrates that through their questions, the pupils were actively involved in guiding their work from various points of views. These results suggest that fifth graders can successfully conduct a complex open inquiry in teams. Consequently, this study underlines that allowing pupils to work at their own pace, and to take responsibility for their learning, opportunities can arise for pupils to pose questions and regulate their learning through questions.